Analysis the influence of proactive personality on employee creativity with thriving at work as a mediator - Jimmy Hennyta Satya Putra; Aryana Satrya (President University, 2022)
Creativity is one of the factors needed by companies to grow and develop in a dynamic environment during uncertain global economic conditions, including the current pandemic Covid-19 condition. This study analyzes the effect of proactive activity on employee creativity in the banking sector. This study also examines thriving at work as a mediating variable in a proactive relationship to employee creativity. The application of Proactive personality behavior reflects how individuals make changes to find solutions. Data were collected from 108 banking employees. Data analysis used the partial least square structural equation modeling (PLS-SEM) technique. The findings reveal that a proactive personality can improve both thriving at work and creativity. Therefore, it is important to support the development of a proactive personality. Moreover, organizations will also benefit from thriving in the workplace to enhance creative behavior by supporting vitality and learning within the organization.